PENGGUNAAN FLUORIDE SECARA SISTEMIK SEBAGAI BAHAN PENCAGAHAN KARIES GIGI PADA ANAK - Sulistiyani, S. (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Dental caries is a process that starts from tooth decay to the email dentin. The success of fluoride because of its ability to penetrate the material, the inhibition of demineralization and remineralization email a high gear, while allowing adaptation caries prevention materials can be attached to the fullest to the tooth structure and can prevent bacterial pertmbuhan. The purpose of writing this paper is to provide information about the use of systemic fluoride as caries prevention in children. Fluorine plays an important role in the prevention of caries and caries control. Fluorine is the most widely antikaries material digunakan.Kadar fluoride used for fluoridation of drinking water from 0.7 to 1 ppm as optimum levels in drinking water can provide maximum protection and effect on caries incidence of dental fluorosis minimal. Fluor as anticariogenic material that can be administered during dental systemically in pre eruption.